Evaluation of physicochemical and antimicrobial properties of creams formulated using Pterocarpus santalinoides seeds methanol extract - Sinodukoo Eziuzo Okafo, Clement Oliseloke Anie, Christian Arerusuoghene Alalor, Lawrence Uchenna Nwankwo (Journal of Applied Pharmaceutical Science, 2023)
To formulate Pterocarpus santalinoides seed methanol extract creams and evaluate them for antimicrobial activity. About 200 g of powdered dried seeds was macerated in 400 ml of methanol for 48 hours, and its collected filtrate was concentrated at 60°C using a rotary evaporator for 6 hours. The antimicrobial activities of the methanol extract against Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Aspergillus niger, and Candida albicans were evaluated. Six cream formulations, P1–P6, were formulated with or without varying the methanol extract concentrations of P. santalinoides. The creams were oil-in-water in nature, with good homogeneity, extrudability, spreadability, and ease of removal. The creams’ pH was between 5.0 ± 0.29 and 5.5 ± 0.17. The viscosities of the formulations ranged from 3,600 to 48,950 mPas at 6 rpm and 1,240 to 6,390 mPas at 60 rpm using spindle 4. The microorganisms used were susceptible to the effect of the methanol extract at 100 mg/ml. All bacteria tested were also susceptible to the creams, but the fungi tested were susceptible only to formulations P4, P5, and P6. Creams with good physicochemical and antimicrobial activities against test organisms were successfully prepared using the methanol extract of P. santalinoides